12-5n=-3(-7n-4)

Simple and best practice solution for 12-5n=-3(-7n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-5n=-3(-7n-4) equation:



12-5n=-3(-7n-4)
We move all terms to the left:
12-5n-(-3(-7n-4))=0
We calculate terms in parentheses: -(-3(-7n-4)), so:
-3(-7n-4)
We multiply parentheses
21n+12
Back to the equation:
-(21n+12)
We get rid of parentheses
-5n-21n-12+12=0
We add all the numbers together, and all the variables
-26n=0
n=0/-26
n=0

See similar equations:

| -2-8i-4-3i=-6-11i | | 7x-2+11x-2+48=180 | | 1.1v−1.8=7.3 | | 4(2+7x)=-20 | | 36n-128=448 | | 5m+9=-16 | | -4(8+5x)=10+x | | 3i-i=2i | | −5(x+3)=20 | | 6x+3=5x-2=39 | | 13^(-5x)=25 | | 8(5r-7)=40+8r | | y/2=15=18 | | 8/x=24/18 | | 1/2x+10=1/4x=54 | | -5+4v=5v+4(5+6v) | | 6-9x-9=-21 | | 12i-7=12i-7 | | e+12=-9 | | 2(9+6x)-3=9x+3(x+5) | | 3/11=11/k | | 12x-108=12 | | 3m+5.25=24.75 | | 107=3-8(2k-5) | | x/50=34/40 | | 98-5q=63 | | 3/11=11k | | -12w2–39=0 | | 34/40=x/50 | | 12i-7i=5i | | 21=x+44 | | 11v-8v=24 |

Equations solver categories